2022
DOI: 10.1021/acs.est.2c04939
|View full text |Cite
|
Sign up to set email alerts
|

Dissimilatory and Cytoplasmic Antimonate Reductions in a Hydrogen-Based Membrane Biofilm Reactor

Abstract: A hydrogen-based membrane biofilm reactor (H2-MBfR) was operated to investigate the bioreduction of antimonate [Sb­(V)] in terms of Sb­(V) removal, the fate of Sb, and the pathways of reduction metabolism. The MBfR achieved up to 80% Sb­(V) removal and an Sb­(V) removal flux of 0.55 g/m2·day. Sb­(V) was reduced to Sb­(III), which mainly formed Sb2O3 precipitates in the biofilm matrix, although some Sb­(III) was retained intracellularly. High Sb­(V) loading caused stress that deteriorated performance that was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Meanwhile, the peak separation analysis indicated that the extracted Sb species comprised a blend of trivalent and zerovalent states, primarily existing as metal oxide (Figure S11c). , Therefore, a logical conclusion can be drawn that the electroreduction products resulting from the Sb­(III) solution constitute a composite of Sb 0 and Sb 2 O 3 .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Meanwhile, the peak separation analysis indicated that the extracted Sb species comprised a blend of trivalent and zerovalent states, primarily existing as metal oxide (Figure S11c). , Therefore, a logical conclusion can be drawn that the electroreduction products resulting from the Sb­(III) solution constitute a composite of Sb 0 and Sb 2 O 3 .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Operated in parallel were two identical MBfRs, shown in Figure S1 and similar to our previous studies. 22,23 Each MBfR comprised a main column containing a 32-fiber bundle and a sampling column containing a 20-fiber coupon bundle for biofilm sampling. The fibers were nonporous polypropylene hollow fibers (Teijin, Japan), which supplied bubble-free H 2 on-demand H 2 to the biofilm attached to the exterior surface.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Recent studies have shown that Sb(V) could also upregulate the expression of the arsC gene, leading to the hypothesis that microbes reduce Sb(V) intracellularly through the As reductase enzyme ArsC and then further detoxify Sb(III) via ArsB. 4 However, the role of ArsC in Sb(V) reduction, at the gene or protein level, remains unverified.…”
mentioning
confidence: 99%
“…Furthermore, both As­(III) and Sb­(III) could trigger As-based defense mechanisms in microbes, manifesting as the upregulated expression of ars gene clusters, facilitating the removal of As­(III) and Sb­(III) from the cells. Recent studies have shown that Sb­(V) could also upregulate the expression of the arsC gene, leading to the hypothesis that microbes reduce Sb­(V) intracellularly through the As reductase enzyme ArsC and then further detoxify Sb­(III) via ArsB . However, the role of ArsC in Sb­(V) reduction, at the gene or protein level, remains unverified.…”
mentioning
confidence: 99%